Reliability of right-to-left shunt screening in the prevention of scuba diving related-decompression sickness. (1st December 2017) - Gempp, Emmanuel; Lyard, Marianne; Louge, Pierre
Abstract: Objectives: The aim of this study was to investigate the relationship between right-to-left shunt (RLS) and the clinical features of decompression sickness (DCS) in scuba divers and to determine the potential benefit for screening this anatomical predisposition in primary prevention. Methods: 634 injured divers treated in a single referral hyperbaric facility for different types of DCS were retrospectively compared to 259 healthy divers. All subjects had a RLS screening by contrast Transcranial Doppler (TCD) ultrasound according to a standardized method. The number of bubbles detected defined the degree of RLS (small if 5–20 bubbles, large if > 20 bubbles). Results: TCD detected 63% RLS in DCS group versus 32% in the control group (p < 0.0001) The overall prevalence of RLS was higher in divers presenting a cerebral DCS (OR, 5.3 [95% CI, 3.2–8.9]; p < 0.0001), a spinal cord DCS (OR, 2.1 [95% CI, 1.4–3.1]; p < 0.0001), an inner ear DCS (OR, 11.8 [95% CI, 7.4–19]; p < 0.0001) and a cutaneous DCS (OR, 17.3 [95% CI, 3.9–77]; p < 0.0001) compared to the control group, but not in divers experiencing ambiguous symptoms or musculoskeletal DCS. There was in increased risk of DCS with the size of RLS. The determination of diagnostic accuracy of TCD testing through the estimation of likelihood ratios revealed that predetermination of RLS did not change significantly the prediction of developing or not a DCS event. Conclusion: The assessment of RLS remains indicated after an initial episode of spinal cord, cerebral, inner ear and cutaneous form of DCS but this approach is definitely not recommended in routine practice.